Asbestos related changes in pulmonary and systemic immune responses--early enhancement followed by inhibition. - Rola-Pleszczynski, M (1982)
We recently developed an animal model in order to study the pulmonary and systemic reactions following exposure to environmental pollutants. In this model, conscious sheep received repeated intratracheal instillations of a suspension of 0 (controls), 2mg (low dose) or 128 mg (high dose) of chrysotile asbestos fibres over a 12 month period. A significant dose-dependent enhancement in proliferative responses of pulmonary free airway cells (FAC) to four mitogens was observed after a first instillation. A somewhat weaker stimulation was also observed in peripheral blood mononuclear leucocytes (PBML). At 6 months, the high dose animals no longer displayed the dose-dependent enhancement of FAC responses and manifested actual depression of PBML responses. At 12 months, all asbestos exposed animals showed impaired responses of FAC, whereas only the PBML of high dose animals were showing such an impairment. These data suggest that asbestos exposure has a dose-dependent initial enhancement of local pulmonary as well as systemic responses to mitogens while prolonged exposure and higher doses can subsequently lead to a relative depression of local and systemic cellular immune activity. Although responsive early after asbestos exposure, systemic immunity appears to lag behind local immunity in the late depressive effect of asbestos fibres on mitogen responsiveness. In addition to these cell-directed effects serum factors seem to play an inhibitory role in lymphocyte responses to mitogens in animals repeatedly exposed to asbestos.